Modeling ancillary effects: improvements in membrane chromatography and Arrhenius-type kinetics - Bower, Shane E., author; Wickramasinghe, Ranil, advisor (Colorado State University. Libraries, 2006)
The time lag created by column peripherals and the column flow distribution headers was modeled for a membrane chromatography system using a Sartorious Q-membrane and bovine serum albumin (BSA). A numerical method was applied that removed the zero order and first order time delays from the breakthrough curve without requiring knowledge of the shape or characteristics of the breakthrough curve in the absence of the time delay. The method was applied to the calculation of Langmuir isotherm parameters under dynamic flow conditions. The Langmuir isotherm calculated under dynamic flow conditions with the time delay removed closely matched the Langmuir isotherm under static (no flow) conditions. The pore size distribution for a 500 kDa molecular weight cut-off cellulose acetate ultrafiltration membrane was determined from the analysis of field emission scanning electron microscopy (SEM) images. A log-normal distribution was fit to the discrete pore size distribution data by both pore radius and normalized flow. The discrete distribution and both continuous distributions were used to calculate membrane flux and Dextran rejection profiles and compared to experimental results. Improvements in flux predictions were made when modeling the pore size distribution based on normalized flow through the discrete pore size distribution. The flux calculations were in strong agreement with the experimental results and the rejection calculations were in good agreement with the experimental results. Agricultural and herbaceous feedstocks may contain appreciable levels of sucrose. The survivability of sucrose and its hydrolysis products, fructose and glucose, was evaluated during dilute sulfuric acid processing over conditions typically used to pretreat lignocellulose biomass. Temperatures from 160-200 °C, acid concentrations from 0.1 to 2.0 %(w/w) sulfuric acid, and reaction times from 3 to 12 minutes were used for the pretreatment conditions. No residual sucrose was detected for any of the conditions, but appreciable concentrations of fructose and glucose were detected under most pretreatment conditions. Different mathematical approaches were used to fit the kinetic parameters for acid-catalyzed thermal degradation of these sugars. Since both sugars may survive dilute acid pretreatment, they could provide an additional carbon source for production of ethanol and other bio-based products.
Keywords: chemical engineering